Utilidad de un visor Dicom para dispositivos móviles en la valoración remota de tomografías de pacientes con traumatismo craneoencefálico en el Hospital Isidro Ayora de Loja. - Salas Guerrero, Ronald Fabricio (2018)
Cranioencephalic trauma (CET) is one of the leading causes of death and the use of computerized axial tomography (CAT) to diagnose TBI is important, however, a workstation for reading medical images is not always available when the specialist The image is not available or is outside the hospital. Modern mobile devices allow real-time interpretation of radiology studies, so it is important to evaluate the reliability of using a mobile device for reading medical images in our environment; with which we set ourselves as objectives: to determine the reliability of the Dicom "OsiriX HD" reader in mobile devices in the remote reading of CT of patients with TBI and its limitations; the precision in determining the Score Rotterdam and; the utility when characterizing bruises, brain contusions and fractures. A CT scan was performed on 57 patients diagnosed with TBI; their studies were downloaded remotely in a workstation and on a mobile device; Two imaging readers were designated who performed the reading independently with the same number of images and sequences. When identifying the Rotterdam Score there were no significant discrepancies, the fractures coincided in 99.12%, intraaxial injuries coincided with 99.13%, the size and density showed insignificant differences showing that mobile device can be as precise as a workstation since it does not shows evidence indicative of disagreements when compared to a workstation dedicated to reading medical images. Keywords: Radiology, computer science, teleradiology, smartphone.